Lateral Extra-Articular Tenodesis as an Adjunct to ACL Reconstruction - Madeline M. McGovern MD; Sercan Yalcin MD; Natalie A. Lowenstein MPH; Jillian L. Mazzocca BA; Elizabeth G. Matzkin MD; Giovanna Medina MD, PhD (Video Journal of Sports Medicine)
Background: Lateral extra-articular tenodesis (LET) is a surgical technique used to decrease the risk of anterior cruciate ligament reconstruction (ACLR) failure by supplementing internal rotational stability and reducing pivot shift. Indications: A growing body of literature indicates that LET should be performed for patients under 25 years, those with increased posterior tibial slope and ligamentous laxity, and elite athletes in cutting and/or pivoting sports. Additional indications include patients with grade 2 pivot shift or greater and those with a history of anterior cruciate ligament graft failure. Technique Description: Surgeon preference determines LET and ACLR sequence. Anatomic landmarks are identified and marked. A 5-cm incision is made in line with the iliotibial (IT) band from Gerdy's tubercle toward the lateral epicondyle. Dissection is carried to the IT band. Approximately 1 cm from the posterior border of the IT band, a full-thickness graft of 7 to 8 cm in length and 1 cm in width is harvested proximally and then whipstitched. A varus stress applies ligamentous tension and aids in lateral collateral ligament (LCL) identification. The LCL is dissected out, and the graft is passed underneath it. An all-suture anchor placed approximately 1 to 2 cm proximal and posterior to the lateral epicondyle and the knee is positioned in neutral rotation and at approximately 60° of flexion. The graft is passed inside the suture loop with an additional knot tied over the top using the needled suture. The IT band is then repaired side to side. Remaining subcutaneous tissue and skin are closed in standard fashion based on the order of the surgery. Results: In the STABILITY randomized controlled trial, 2-year outcomes demonstrated a clinically and statistically significant decrease in clinical failure from 40% to 25% and graft rupture rate from 11% to 4% with the addition of LET to ACLR with hamstring autograft. Similar return-to-sport rate was seen between cohorts. A meta-analysis of 6 studies examining ACLR versus ACLR + LET in individuals undergoing primary ACLR reported a reduced incidence of graft failure and postoperative anterolateral rotatory instability. Discussion/Conclusion: LET is a technique that can help reduce the risk of ACLR failure. Our technique employs a knotless suture anchor to confer anterolateral rotatory stability in the setting of ACLR. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.